Tax deduction or financial subsidy during crisis? Effectiveness of fiscal policies as pandemic mitigation and recovery measures - Jean Jinghan Chen; Richard T. R. Qiu; Eden Xiaoying Jiao; Haiyan Song; Yuanjie Li (Annals of Tourism Research Empirical Insights, 2023)
Economic analysis of the tourism industry is a critical tool for local industries and governments to estimate, understand, and forecast the tourism potential and economic performance of a destination, especially amidst a crisis such as the COVID-19 pandemic. In this study, we take Macao as a case study, perform an analysis using an input-output framework. By constructing a tourism satellite account and a dynamic stochastic general equilibrium model, we estimate the contribution of the tourism industry to the economy of Macao and assess the ramifications of several government policies to mitigate the impact of COVID-19. Our findings provide the Macao government and local industrial stakeholders with critical information for pandemic mitigation and recovery strategies.
Keywords: 330; Macao tourism industry; Input-output framework; Tourism satellite account; Dynamic stochastic general equilibrium model; Pandemic mitigation policy